2014
DOI: 10.2466/24.22.pms.118k22w4
|View full text |Cite
|
Sign up to set email alerts
|

Co-Witness Auditory Memory Conformity following Discussion: A Misinformation Paradigm

Abstract: Twenty-four Japanese undergraduate pairs (12 male and 12 female pairs) participated as witnesses to a simulated criminal event. Although the witness pairs watched the same video together, through wireless headphones they experienced two different auditory versions with four differing items without being aware of the discrepancies. After the presentation, the witnesses were led to discuss six items, including two critical ones they had heard differently and another four they had heard in common. Witness memory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Skagerberg and Wright () demonstrated that when pairs of individuals viewed and discussed different versions of the same event, they combined their memory reports and each individual recalled misleading details based upon the recollection of others. Similarly, Mori and Kishikawa () reported that CWs combined reports and recalled more misleading information about key event details after a discussion. Such results suggest actual changes or alterations in memory, rather than compliance to the social situation.…”
mentioning
confidence: 96%
“…Skagerberg and Wright () demonstrated that when pairs of individuals viewed and discussed different versions of the same event, they combined their memory reports and each individual recalled misleading details based upon the recollection of others. Similarly, Mori and Kishikawa () reported that CWs combined reports and recalled more misleading information about key event details after a discussion. Such results suggest actual changes or alterations in memory, rather than compliance to the social situation.…”
mentioning
confidence: 96%
“…Research focusing on memory conformity has been reported for about two decades now, and has used different types of materials, such as pictorial (Wright et al, 2000;Goodwin, Kukucka, & Hawks, 2013;Meade & Roediger, 2002), and auditory stimuli (Mori & Kishikawa, 2014;Oeberst & Siedemann, 2014). Several memory conformity studies involved the presentation of short movies, and the interaction of a naïve participant with a confederate (i.e., typically an actress or actor).…”
mentioning
confidence: 99%